Strategi Pembelajaran Tematik - Musfirah, Nurul; U, Usman; U, M. Shabir (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the thematic learning strategy. Given that in modern times today, education issues are very important. Thematic Learning is integrated learning that uses themes to link several subjects so that it can provide meaningful experiences to students. This research is the result of a study or literature review sourced from library literature or library materials, both in the form of books and articles published through printed and online scientific journals. The focus of the study in this article is on thematic learning strategies that are relevant to Islamic religious education learning. The data obtained are reviewed/analyzed and then presented descriptively in the form of an article. The results of the study show that the implementation of thematic learning every day is carried out using three stages of activity, namely opening/initial/introduction activities, core activities and closing activities. The conclusion is that Thematic Learning is integrated learning that uses themes to link several subjects so that it can provide meaningful experiences to students. Theme is the main idea or main idea that is the main topic of discussion.